Influence of Political Ideology on Perceptions of Mask Wearing and Microaggressions (London Journal of Research In Humanities and Social Sciences, 2023)
This exploratory study aimed to examine college students (N = 237) perceptions of mask- wearing related to political ideology and the potential for microaggressions to arise due to these perceptions. Data were collected using an online survey through Qualtrics. Analyses revealed that conservative-leaning participants reported significantly higher instances of aggression toward people not wearing masks (M = 3.52, SD = 1.28) than those leaning liberal (M = 2.53, SD = 1.39), t(151) = 3.19, p & lt; .001). Interestingly, no significant mean difference was found between conservatives and liberals regarding microaggressions toward mask and mask-less behavior. Finally, those leaning liberal are statistically more likely to believe that the reason that people do not wear face masks is that they do not care about others (M = 2.30, SD = 1.30, t(149) = 3.90, p < .001). Conclusions for why political ideologies affect perceptions of mask-wearing and potential microaggressions are provided.
Keywords: political ideology; polarization; identity development; microaggressions; mask-wearing